PENERAPAN TEKNOLOGI WEB SEKOLAH BAGI SMP DAN SMA MUHAMMADIYAH KARTASURA - Supriyono, Heru; Sutopo, Anam; Nursyahid, Hamdani; Kurniawan, Bryan Anthony; Fahrudin, Irfan Nur; Handoko, Donny; Rivai, Imam; Kurniawan, Dwi Cahyo (Universitas Muhammadiyah Surakarta, 2016)
Observation and interview with headmasters, teachers and administrative employees results showed that one of main problems faced by SMP Muhammadiyah 1 Kartasura and SMA Muhammadiyah 4 Kartasura is the do not have a representative school website. Based on this observation, after making discussion with headmasters, the community services team proposed an implementation of school website and train one of chosen teacher to manage implemented website. The outcomes of the community service activities are involving a school website for SMP Muhammadiyah 1 Kartasura and SMA Muhammadiyah 4 Kartasura and scientific publication draft. The contribution of each school is including providing information which will be uploaded to the website, providing fee for domain and hosting cost, and providing facilities for administrator training. The duration of this commuity services is three months. The results of the community services is both SMP Muhammadiyah 1 Kartasura dan SMA Muhammadiyah 4 Kartasura are now have representative website for their promotion and administative activities.